TRADITIONS OF JAPANESE GARDEN AND PARK ART IN THE CONDITIONS OF THE MODERN CITY (ON THE EXAMPLE OF KYIV) - Михайлова, Р. Д.; Вишневська, О. В.; Ясько, С. В. (Art and Design, 2021)
The purpose of the article is to analyze the Japanese art of gardening in its tangible and intangible dimensions. The phenomenon of landscape art is considered in the context of the values of authenticity, typology and its aesthetic value in the city. Methodology.The research uses general scientific methods of analysis; comparative method, typological systematization, historical-chronological method, methods of art analysis. The results. To clarify the essence of the Japanese gardening art phenomenon, this work presents the history and conditions of its origin, its stages of development, as well as the current state. Also, typical garden and park architectural and planning solutions, based on traditional Japanese designs and most often used in the arrangement of parks and gardens, were revealed. Various models of a Japanese park/garden and its temporary transformations in an urban environment were considered; as well as options for design architectural and spatial solutions, most common in modern landscape art. A variant of the design solution for the Kyoto park in Kyiv was revealed, among other things. As a result, a general picture of the current level of development of the Japanese garden park was formed, and its features as an art and design object were emphasized. The scientific novelty of the work is to study the Japanese tradition of landscaping in modern cities and to identify objective approaches to determining its landscape-spatial and artistic elements, taking into account specific varieties on the example of Kyoto Park in Kyiv. Practical significance. Scientific research of the history, traditions and types of formation of a Japanese park / garden in a modern city can be used in architectural and spatial landscape solutions to create specific patterns with expressive artistic features.